CYBER-PR DALAM E-MUSRENBANG DI PEMERINTAH KOTA TANGERANG SELATAN - Amin Shabana; Tria Patrianti (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
Since the launch of decentralization, the Musrenbang (Musyawarah Rencana Pembangunan) or Multi Stakeholder Consultation Forum for Development Planning is the principal instrument introduced by the Government of Indonesia for public consultation. In support of this participatory Musrenbang process, a number of regional governments including South Tangerang, have tried to increase participation by developing an online Public relations system. It is addressed to legislate transparency in budgeting and deepen the consultative approach down to the community level. The said system is electronic Musrenbang (e-Musrenbang) coordinated by Bappeda (City Development Planning Agency) together with disctrict level (Kecamatan). This research aimed to seek how the utilization of Cyber PR in Musrenbang by City Development Planning Agency of South Tangerang (Bappeda). Using qualitative data and case study method, the research conducted through in-depth interviews and FGD with bureaucrats in Bappeda, sub-district, village, and neighbourhood. E-Musrenbang as one of the concepts of Cyber PR conducted in Bappeda Tangerang Selatan, needs to be improved. This is to foster the use the application and the involvement of stakeholders for better Tangerang Selatan in the future.